Structural analysis of polarizing indels: an emerging consensus on the root of the tree of life - Bourne Philip E (Biology Direct, 2009)
Abstract Background The root of the tree of life has been a holy grail ever since Darwin first used the tree as a metaphor for evolution. New methods seek to narrow down the location of the root by excluding it from branches of the tree of life. This is done by finding traits that must be derived, and excluding the root from the taxa those traits cover. However the two most comprehensive attempts at this strategy, performed by Cavalier-Smith and Lake et al., have excluded each other's rootings. Results The indel polarizations of Lake et al. rely on high quality alignments between paralogs that diverged before the last universal common ancestor (LUCA). Therefore, sequence alignment artifacts may skew their conclusions. We have reviewed their data using protein structure information where available. Several of the conclusions are quite different when viewed in the light of structure which is conserved over longer evolutionary time scales than sequence. We argue there is no polarization that excludes the root from all Gram-negatives, and that polarizations robustly exclude the root from the Archaea. Conclusion We conclude that there is no contradiction between the polarization datasets. The combination of these datasets excludes the root from every possible position except near the Chloroflexi. Reviewers This article was reviewed by Greg Fournier (nominated by J. Peter Gogarten), Purificación López-García, and Eugene Koonin.